Dorothy Clotelle Clark, Allegory, Decalogue and deadly sins in "La Celestina". University of California Press, Berkeley and Los Angeles, 1968; 136 pp. (UCPMP, 91). - Kersten, Raquel (Nueva Revista de Filología Hispánica (NRFH), 1972)
Se reseñó el libro: Allegory, Decalogue and deadly sins in "La Celestina".